2008
DOI: 10.1152/jn.90257.2008
|View full text |Cite
|
Sign up to set email alerts
|

Canal and Otolith Contributions to Compensatory Tilt Responses in Pigeons

Abstract: McArthur KL, Dickman JD. Canal and otolith contributions to compensatory tilt responses in pigeons. J Neurophysiol 100: 1488 -1497, 2008. First published July 16, 2008 doi:10.1152/jn.90257.2008. Gazestabilizing eye and head responses compensate more effectively for low-frequency rotational motion when such motion stimulates the otolith organs, as during earth-horizontal axis rotations. However, the nature of the otolith signal responsible for this improvement in performance has not been previously determined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…In a previous study, we demonstrated that pigeons integrate canal and otolith signals to generate compensatory responses to EHA rotation (McArthur and Dickman 2008). Thus, we transformed the maximum sensitivity vectors for canal (α CANAL ) and otolith (α OTO ) response components, to predict each component’s maximum sensitivity vector for EHA rotation (see Methods for details).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous study, we demonstrated that pigeons integrate canal and otolith signals to generate compensatory responses to EHA rotation (McArthur and Dickman 2008). Thus, we transformed the maximum sensitivity vectors for canal (α CANAL ) and otolith (α OTO ) response components, to predict each component’s maximum sensitivity vector for EHA rotation (see Methods for details).…”
Section: Resultsmentioning
confidence: 99%
“…For pigeons and other lateral-eyed animals, both canal and otolith stimulation contribute to compensatory eye and head responses that stabilize gaze during rotation relative to gravity (i.e. EHA rotation; pigeon: Dickman and Angelaki 1999; Dickman, Beyer and Hess 2000; McArthur and Dickman 2008; mouse: Harrod and Baker 2003; rat: Brettler et al 2000; rabbit: Barmack 1981). Specifically in pigeons, we have demonstrated that a dynamic net head-horizontal linear acceleration signal improves the phase of both eye and head responses to EHA tilt (McArthur and Dickman 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For rotational stimuli, neural gains were expressed as the peak change in IFR (spk/s) relative to peak angular velocity (°/s), and phase values were expressed relative to peak positive angular velocity. Responses to translational stimuli were expressed relative to the apparent tilt-that is, the earth-horizontal axis rotation that would produce the equivalent linear acceleration stimulus in the head (McArthur and Dickman, 2008). For example, an x-axis (fore-aft) translation (0.5 Hz, 0.1G) would correspond to an apparent y-axis (pitch) tilt (0.5 Hz, Ϯ6°, ϳ20°/s), allowing us to directly compare neural responses to these two stimuli where the linear acceleration stimulus to the animal was matched.…”
Section: Methodsmentioning
confidence: 99%